1992
DOI: 10.1177/01454455920161006
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Heart Rate Reactivity to Stress with Feedback Generalization Across Task and Time

Abstract: Heart rate (HR) reactions to two behavioral stressors (videogame and mental arithmetic) were measured in 8 experimental subjects who received biofeedback training and 8 matched control subjects during three assessment periods: pretraining, posttraining, and one-week follow-up. Experimental subjects exhibited significant reductions in HR following a training session in which they received ongoing HR feedback while playing a videogame. Control subjects, who played the same number of videogames without HR feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…The mean HR response of those selected for the study ranged from 13 bpm (i.e., participant 13) to 22 bpm (i.e., participant 4) compared to a range of 0 bpm (i.e., participant 7) to 10 bpm (i.e., participant 12) for those not selected to participate in the study. Those selected for the study demonstrated HR responses within the ranges of HR responses observed in other studies (e.g., Goodie & Larkin, 2001;Larkin et al, 1992a). After participant 6 dropped out of the study (mean HR response = 20 bpm), participant 13 was selected to replace him.…”
Section: Heart Rate Responsementioning
confidence: 99%
See 4 more Smart Citations
“…The mean HR response of those selected for the study ranged from 13 bpm (i.e., participant 13) to 22 bpm (i.e., participant 4) compared to a range of 0 bpm (i.e., participant 7) to 10 bpm (i.e., participant 12) for those not selected to participate in the study. Those selected for the study demonstrated HR responses within the ranges of HR responses observed in other studies (e.g., Goodie & Larkin, 2001;Larkin et al, 1992a). After participant 6 dropped out of the study (mean HR response = 20 bpm), participant 13 was selected to replace him.…”
Section: Heart Rate Responsementioning
confidence: 99%
“…Scores after each trial were recorded. This videogame task has been used to teach HR feedback in previous studies (Goodie & Larkin, 2001;Larkin et al, 1989Larkin et al, , 1990Larkin et al, , 1992aLarkin et al, , 1992b.…”
Section: Videogamementioning
confidence: 99%
See 3 more Smart Citations